Study Of The Nature Of Batang Nibung (Oncosperma tigillarium ) In The Village Of Tameran, Bengkalis Regency - Nur Hasanah; Rudianda Sulaeman; Evi Sribudiani (Jurnal Ilmu Ilmu Kehutanan, 2019)
There are still many nibung stems on Bengkalis area especially in Temeran village. According to Nurlia, et al., (2013) in general use stem nibung done from generation to generation. The purpose of this study is Knowing anatomical properties nibung stem which covers the vascular bundles, parenchyma and nibung stem fibers. Knowing the physical properties of the nibung stem according to the height and depth of the stem including the water content, density, specific gravity and three-way shrinkage. Knowing the mechanical properties of the nibung stem which includes MOE (Modulus of Elasticity) and MOR (Modulus of Rupture). Properties The anatomy of the nibung stem shows that it is dominated by vascular bundles at the base then dominated by the parenchyma at the end. The color of the black nibung stem is striped on the skin and the color of the cream on the center of the skin and the basting. The physical properties of the nibung stem show that the skin edge of the nibung stem can be used as a lightweight construction because it has an average density value of 0.53 g. Cm-3, which is included in the strong class III. As for the center and pith section it is not recommended to be used as a construction, because the average density is 0.28 g.cm-3 in the middle and an average of 0.17 g.cm-3 in the pith section is included in the strong class V. The mechanical properties of the nibung stem were seen from the highest MOE and MOR values found on the edges of the skin, with an average MOE value of 584.78 kg.cm-2. Likewise for the MOR value the biggest nibung stem is found on the edge of the skin with a value of 432,527 kg.cm-2, and on the edges of the skin including the strong class II and the middle and the bile included in the strong class V.